Innovation of helical cutting tool edge for eco-friendly milling of wood-based materials. Issue 6 (2nd November 2022) - Pangestu, Kidung Tirtayasa Putra; Nandika, Dodi; Wahyudi, Imam; Usuki, Hiroshi; Darmawan, Wayan
ABSTRACT: An extreme inclination angle of helical cutting tool edge has been developed in milling of new commercially wood-based materials. The purpose of this research was to investigate wear resistance, chip flow and shape, surface roughness, and noise level of helical edge cutting tools in milling wood-based materials. The wood-based materials of wood plastic composite, laminated veneer lumber, and oriented strand board were cut by the helical edge cutting tools (inclination angle of 15°, 30°, 45°, 60°, and 75°) in the up-milling and down-milling processes on a computer numerical control router. Feed speed was set up in 2, 3, and 4 m/min. The results show that the helical edges provide better wear resistance, better surface quality, and lower noise emission compared to the conventional edge (0°). Edge radius wear, chip flow area and flight speed, surface roughness, and noise level decreased with increasing the inclination angle of the cutting tool edges. The differences in the wood-based material structure, the milling process, and the feed speed resulted in the difference in cutting tool wear, chip flow and shape, surface roughness, and noise level phenomenon.